Faktor-Faktor Penentu Tingkat Pemahaman Akuntansi - Edy Suprianto; Septian Harryoga (Fakultas Ekonomika dan Bisnis Universitas Kristen Satya Wacana, 2015)
Framework for the Development of Accounting Education Research which ispromulgated by the American Accounting Association (AAA), state that special research for accounting education is a need. Tikollah et al. (2006) found that the degree of accounting knowledge is increased by emotional intelligence and students’ self-confidence. This study tries to evaluate the effect of emotional intelligence, study behavior, and culture to the degree of accounting knowledge that is moderated by self confidence. The research population is all of the students in Semarang. While the samples were collected using purposive sampling method. There are two criteria tochoose the samples; which are (1) student from the accounting department in sixth until eighth semester, and (2) the students in Sultan Agung Islamic University, Diponegoro University and Semarang State University. Based on these criteria, the samples are counted by 96 students. The result revealed that emotional intelligence and study behavior has a significant positive effect to the degree of accounting knowledge. Culture does not have a significant effect to the the degree of accounting knowledge. Moreover, the research could not provide evidence that self-confidence is a moderating variable to increase degree of accounting knowledge.